Implementation of Backtracking Algorithm in Determining Operation Schedule - Warianti, Sri; Sutabri, Tata (International Journal Scientific and Professional, 2025)
Scheduling surgical operations in hospitals is a complex process requiring efficient allocation of limited resources such as specialist doctors, operating rooms, and time slots. This study implements the backtracking algorithm to create an optimal surgery schedule from Monday to Thursday, involving 8 specialist doctors (3 general surgeons and 5 obstetricians-gynecologists), and 1 orthopedic surgeon who is available only on Wednesdays and Thursdays. With 4 operating rooms and 5 sessions per day, the backtracking algorithm explores all possible scheduling combinations to avoid conflicts in time and location. The implementation results show that the algorithm successfully generates a conflict-free schedule while also assigning on-call doctors for emergency (cito) cases in surgery, obstetrics-gynecology, and orthopedics. Visualization in Excel tables and daily graphical layouts aids in verification and intuitive interpretation. This approach proves effective in handling complex and dynamic hospital scheduling scenarios.